Multimeter Portabel Pengukur Nutrisi Tanah Pertanian untuk Kelompok Tani Maju Mandiri di Pulau Setokok - Gozali, Muhammad Syafei; Kamarudin, Kamarudin; Wijanarko, Heru; Futra, Asrizal Deri; Darmoyono, Aditya Gautama; Oktani, Dessy; Hasnira, Hasnira; Mahdaliza, Rahmi; Lubis, Eka Mutia; Wicaksono, Muhammad Jaka Wimbang; Pamungkas, Daniel Sutopo; Zaenuddin, Muhammad; Setiawan, A. Rido; Zulmi, Muhammad Afif; Ginting, Pedro Imanuel; Pasaribu, Cindy Kristine; Amiruddin, Amiruddin (Politeknik Negeri Batam, 2023)
Today, the current development of Batam City is not only in the development of industrial and tourism areas but also leads to the development of agriculture and plantations. This was done as a form of effort in maintaining food security for areas in Batam City, where initially a lot of food needs were supplied from areas on the island of Sumatra. The city of Batam, whose territory consists of islands, creates obstacles in the development of agricultural land and plantations. Among them are types of soil that are difficult for seasonal crops to grow; water resources that depend on rainwater; as well as access to agricultural and plantation locations that are spread across several islands, making it difficult to deliver logistics and agricultural products. Soil conditions greatly affect the quality of the plants produced, and the type of soil will affect the types of plants suitable for planting. Based on these obstacles, the Batam State Polytechnic formed a Community Service team to support the agricultural land development program, one of which was the development team for portable soil condition measuring devices in collaboration with a partner from